2021
DOI: 10.1515/nanoph-2020-0644
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the surface-enhanced Raman spectroscopy (SERS) activity and plasmon-driven catalytic efficiency by the control of Ag NP/graphene layers under optical excitation

Abstract: Highly efficient plasmon-driven catalysis and excellent surface-enhanced Raman spectroscopy (SERS) performance are proportional to the square of the local electromagnetic field (hot spot). However, a proven way to realize the enhancement in intensity and density of “hot spot” still needs to be investigated. Here, we report on multilayered Ag nanoparticle (Ag NP)/graphene coupled to an underlying Cu film system (MAgNP-CuF) which can be used as an effective SERS substrates realizing ultra-sensitive detection for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 38 publications
0
18
0
1
Order By: Relevance
“…However, the instability of the metals, susceptible to oxidation and sulfidation, could hinder the efficiency and consistency of the substrate for creating a plasmonic hotspot, thereby decreasing the sensitivity of the target molecules. Besides the metal nanoparticles (NPs), several semiconductors have also been used as SERS sensing materials, such as TiO 2 , MoS 2 nanostructures, CuTe nanocrystals, Cu 2 O nanospheres, InAs/GaAs quantum dots, and graphene and its derivatives. However, the SERS sensitivity of semiconductors is relatively low as compared to that of metal NPs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the instability of the metals, susceptible to oxidation and sulfidation, could hinder the efficiency and consistency of the substrate for creating a plasmonic hotspot, thereby decreasing the sensitivity of the target molecules. Besides the metal nanoparticles (NPs), several semiconductors have also been used as SERS sensing materials, such as TiO 2 , MoS 2 nanostructures, CuTe nanocrystals, Cu 2 O nanospheres, InAs/GaAs quantum dots, and graphene and its derivatives. However, the SERS sensitivity of semiconductors is relatively low as compared to that of metal NPs.…”
Section: Introductionmentioning
confidence: 99%
“…21 In these reports, the PDSC reactions basically occur on the metal−air/water surface. In recent years, it has been reported that the PDSC reactions can occur at the metal−medium interface, such as metal−graphene, 22,23 order to further assist the application of heterogeneous catalysis in new applications and the design of new catalyst materials. Therefore, the PDSC reactions at the interface are a frontier topic worthy of attention.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In these reports, the PDSC reactions basically occur on the metal–air/water surface. In recent years, it has been reported that the PDSC reactions can occur at the metal–medium interface, such as metal–graphene, , metal–TiO 2 , metal–MoS 2 , and so on. Adjusting the optical and electrical properties of the medium helps to understand the potential kinetics and mechanisms of the catalytic reaction in order to further assist the application of heterogeneous catalysis in new applications and the design of new catalyst materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the electromagnetic field intensity is inversely proportional to the distance parameter, which means that the effective SERS signal is generated on the premise that the molecule is located in the confined area around the plasmonic material [10]. Various types of SERS substrate structures ranging from nanoparticle (NP) aggregates [11][12][13][14][15], multidimensional structure [16][17][18][19][20] and composite substrate [21][22][23][24][25][26][27][28][29] were prepared to explore the better enhancement factor (EF) under various conditions. Among them, the cavity system has been paid more and more attention because of its unique light trapping characteristics [30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%